Farm dust resistomes and bacterial microbiomes in European poultry and pig farms. (October 2020) - Luiken, Roosmarijn E.C.; Van Gompel, Liese; Bossers, Alex; Munk, Patrick; Joosten, Philip; Hansen, Rasmus Borup; Knudsen, Berith E.; García-Cobos, Silvia; Dewulf, Jeroen; Aarestrup, Frank M.; Wagenaar, Jaap A.; Smit, Lidwien A.M.; et al.
Highlights: An analysis of farm dust from 79 pig and poultry farms using metagenomics. Farm dust resistomes are compared to animal fecal and farmers stool resistomes. Farm dust bacterial microbiomes have an abundant and rich resistome. Animal fecal resistomes are an important, but not the only, source of farm dust ARGs. Antimicrobial usage in the animals is positively associated with dust resistome abundance. Abstract: Background: Livestock farms are a reservoir of antimicrobial resistant bacteria from feces. Airborne dust-bound bacteria can spread across the barn and to the outdoor environment. Therefore, exposure to farm dust may be of concern for animals, farmers and neighboring residents. Although dust is a potential route of transmission, little is known about the resistome and bacterial microbiome of farm dust. Objectives: We describe the resistome and bacterial microbiome of pig and poultry farm dust and their relation with animal feces resistomes and bacterial microbiomes, and on-farm antimicrobial usage (AMU). In addition, the relation between dust and farmers' stool resistomes was explored. Methods: In the EFFORT-study, resistomes and bacterial microbiomes of indoor farm dust collected on Electrostatic Dust fall Collectors (EDCs), and animal feces of 35 conventional broiler and 44 farrow-to-finish pig farms from nine European countries were determined by shotgun metagenomic analysis. The analysis also included 79 stool samples from farmers working or living at 12 broiler and 19 pig farms and 46 human controls. Relative abundance of and variation in resistome and bacterial composition of farm dust was described and compared to animal feces and farmers' stool. Results: The farm dust resistome contained a large variety of antimicrobial resistance genes (ARGs); more than the animal fecal resistome. For both poultry and pigs, composition of dust resistomes finds (partly) its origin in animal feces as dust resistomes correlated significantly with fecal resistomes. The dust bacterial microbiome also correlated significantly with the dust resistome composition. A positive association between AMU in animals on the farm and the total abundance of the dust resistome was found. Occupational exposure to pig farm dust or animal feces may contribute to farmers' resistomes, however no major shifts in farmers resistome towards feces or dust resistomes were found in this study. Conclusion: Poultry and pig farm dust resistomes are rich and abundant and associated with the fecal resistome of the animals and the dust bacterial microbiome.